2007
DOI: 10.1021/es070099a
|View full text |Cite
|
Sign up to set email alerts
|

Cost Structure of a Postcombustion CO2 Capture System Using CaO

Abstract: This paper presents the basic economics of an emerging concept for CO2 capture from flue gases in power plants. The complete system includes three key cost components: a full combustion power plant, a second power plant working as an oxy-fired fluidized bed calciner, and a fluidized bed carbonator interconnected with the calciner and capturing CO2 from the combustion power plant. The simplicity in the economic analysis is possible because the key cost data for the two major first components are well establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(177 citation statements)
references
References 4 publications
8
168
0
1
Order By: Relevance
“…For the lowest PCO2 , the first 'wet' carbonation started at a lower temperature than the 'dry' one. It is worth noting that the temperatures where the carbonations began in this study were significantly lower than those reported in the literature (Abanades et al 2007;Chrissafis, Dagounaki, and Paraskevopoulos 2005a). This could be attributed to the non-isothermal conditions of the experiments, which allowed for the kinetic data generation from ambient to high temperatures, as opposed to the kinetic studies so far carried out at high-temperature isothermal conditions.…”
Section: The Effect Of Steammentioning
confidence: 67%
See 1 more Smart Citation
“…For the lowest PCO2 , the first 'wet' carbonation started at a lower temperature than the 'dry' one. It is worth noting that the temperatures where the carbonations began in this study were significantly lower than those reported in the literature (Abanades et al 2007;Chrissafis, Dagounaki, and Paraskevopoulos 2005a). This could be attributed to the non-isothermal conditions of the experiments, which allowed for the kinetic data generation from ambient to high temperatures, as opposed to the kinetic studies so far carried out at high-temperature isothermal conditions.…”
Section: The Effect Of Steammentioning
confidence: 67%
“…in fuel cells. Calcium looping particularly proved to be the cheapest option for CO2 capture (Romeo et al 2009) based on CO2 avoided cost (Abanades et al 2007). Moreover, materials are sought for CO2 capture, which will reduce the energy consumption by increasing the production efficiency of the energy carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The contents of the main emerging trends in the CCS technology include at least the following aspects: (1) Emerging techniques and processes. With the development of science and technology, relevant techniques and processes have been developed and applied in CCS technology, such as postcombustion [69,70,98], combustion synthetic method [72], calcium looping technology [73,74], amine-functionalized solids and amine-scrubbing technique [75,76], facile nucleophilic substitution reaction [78], and so on. (2) Emerging materials.…”
Section: Discussionmentioning
confidence: 99%
“…Abanades et al [69] described that CCS technology can be considered as one of the significant technical means to cope with climate change, and it is necessary to analyze the economical expenditure to explore the potential paths of utilizing carbon capture technology. They analyzed that the most common form of the cost estimation of carbon capture is incremental expenditure in power and the expenditure in removing the CO 2 .…”
Section: Main Contents Of Important Emerging Trendsmentioning
confidence: 99%
“…High-temperature post-combustion removal (HT-CCS) by carbonate looping has been identified by The European Technology Platform for Zero-Emission Power Generation (ZEP) as one of the most promising methods in the developing stage [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The concept relies on absorption of CO 2 by CaO with formation of CaCO 3 in the solid state.…”
Section: Introductionmentioning
confidence: 99%